(untitled) (Journal of Patan Academy of Health Sciences, 2020)
Introduction: Awareness and attitude regarding human immunodeficiency virus and acquired immunodeficiency syndrome (HIV/AIDS) can play a crucial role in providing health education and prevention of HIV/AIDS. This study aims to find out awareness and attitude regarding HIV/AIDS amongst secondary level school teacher. Method: During 3-months period in 2018, secondary level school teachers in Lalitpur district in Kathmandu valley, Nepal, were randomly selected by lottery to find out their awareness and attitude regarding HIV/AIDS. A self-administered structured questionnairesand a five-points Likert attitude scale was used to collect data. Data was analysed with SPSS version 16. Result: Among 116 school teachers included in the study, 94 (81%) had adequate level of awareness on HIV/AIDS, 115(99.1%) were aware about sexual transmission of HIV, 112 (96.6%) about not being transmitted by eating drinking from same utensils and 113 (97.4%) knew commercial sex workers as high-risk group. Overall, 106 (91.4%) had favourable attitude regarding HIV/AIDS. There was no significant correlation between awareness and attitude. Conclusion: The HIV/AIDS awareness among secondary level school teachers was adequate, their attitude was favorable. There was no association between awareness and attitude.